Modeling the heating of the reservoir near-wellbore zone using an induction heater - Denis V. Kosmylin; Vladimir Ya. Fedotov; Filyus F. Davletshin; Ramil F. Sharafutdinov; Rim A. Valiullin (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. During heavy oil extraction and transportation in the near-wellbore zone of the reservoir and the wellhead, deposits occur. They have a negative impact on the efficiency of oil field development. The paper considers a promising method for cleaning the near-wellbore zone of the reservoir from wax deposits using an induction heater. Aim. The study the features of the thermal field in the near-wellbore zone of the reservoir created by induction heating of the casing in the well. Methods. Numerical mathematical modeling of thermal processes in the near-wellbore zone of the reservoir during induction heating; experimental study of the thermal field on a physical model of a well with an induction heater. Results and conclusions. The authors have proposed the mathematical model for calculating non-stationary temperature field in the near-wellbore zone of the reservoir during induction heating of the casing. Model curves of temperature dynamics over time on the casing wall and in the near-wellbore zone of the reservoir are computed. Using the example of periodic induction exposure, including cycles of operation on and shutdown the heater, it is shown that the radius of propagation of thermal disturbance in the reservoir over a 12-hour exposure period is more than 0.5 m. It was found that the reservoir heating with a value of more than 5 degrees Celsius is achieved in the near-wellbore zone of the reservoir with a radius of 0.2–0.3 m, depending on the thermal conductivity of the rocks. The authors performed the experimental studies of a thermal field in a physical model of a well with an induction heater. It is shown that the reservoir heating with a value of more than 1 degree Celsius is achieved in the radius range up to 0.25 m. The results of numerical and experimental studies show the possibility of using induction heating to clean the near-wellbore zone of the reservoir from wax deposits.